Antistatic dry film protective film and preparation method thereof

By adopting three-layer structure design and the preparation of composite antistatic agents in the dry film protective film, the problems of electrostatic and adhesion instability of the existing dry film protective film are solved, and better antistatic properties and bond stability are achieved. , extends service life and improves the overall quality of dry film.

CN119242198APending Publication Date: 2025-01-03湖北慧狮塑业股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411528534.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing dry film protective film has problems such as large electrostatic electricity and unstable adhesion, which affects the quality and service life of the dry film.

Method used

The three-layer structure design adopts an antistatic dry film protective film, including a matte layer, an adhesive layer and a core layer. The core layer is composed of copolymer polypropylene, polyolefin elastomer and composite antistatic agent, and is modified through the nano-silicon dioxide surface. The composite antistatic agent is prepared by grafting reaction, forming a core layer with excellent antistatic properties, and forming a matte surface layer and an adhesion layer through low-density polyethylene and silicone powder.

Benefits of technology

It significantly reduces static electricity accumulation, improves dust-proof and scratch-proof capabilities and adhesion, extends service life, enhances the efficiency and quality of the processing process, and improves the overall performance and reliability of the dry film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005109894600000151
    Figure BDA0005109894600000151
Patent Text Reader

Abstract

The invention discloses an antistatic dry film protective film and a preparation method thereof, and relates to the technical field of dry film protective films.The dry film protective film is formed by compounding a matt finish layer, an adhesion layer and a core layer, and the core layer is located between the matt finish layer and the adhesion layer; the core layer is prepared from the following components in parts by weight: 60-80 parts of co-polypropylene, 18-40 parts of a polyolefin elastomer and 3-10 parts of a composite antistatic agent; according to the prepared dry film protective film, static electricity accumulation is effectively reduced, the overall performance of the protective film is improved, the protective film has better dustproof and anti-scratching capacity and stable binding power and peelability, the service life of the protective film is prolonged, and the efficiency and quality of the follow-up machining process are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of dry film protective films, and in particular to an antistatic dry film protective film and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of the electronics industry, printed circuit board manufacturing technology has continued to advance. In this process, dry film technology plays a key role. Dry film is a special polymer compound that undergoes polymerization reaction after ultraviolet irradiation to form a stable protective layer for pattern transfer and etching protection of circuit boards.

[0003] Dry film usually consists of three layers: a top protective film, a middle photosensitive layer and a bottom carrier layer. The top protective film is mainly used to protect the photosensitive layer from the external environment; the middle photosensitive layer is the core of the dry film, composed of photosensitive resin, which can undergo polymerization under ultraviolet light; the bottom carrier layer is usually made of polyester (PET) material to provide support for the entire dry film structure. Before use, the top and bottom protective layers need to be peeled off to ensure that the photosensitive layer can directly contact the surface of the circuit board.

[0004] In the production process of dry film, the photosensitive layer is first coated on the carrier, and then covered with a protective film to form a complete dry film structure. This three-layer structure design is not only convenient for the storage and transportation of dry film, but also effectively protects the performance of the photosensitive layer.

[0005] Dry film protective film plays a vital role in the entire production and use process. It not only maintains the flatness and transparency of the dry film surface, but also prevents the dry film from deformation and damage. In addition, the protective film also has anti-static and anti-scratch functions, effectively preventing the intrusion of dust and pollutants, slowing down the aging process of the dry film, and thus extending its shelf life.

[0006] At present, the common dry film protective film materials on the market are mainly polyethylene (PE) and polypropylene (PP), and these two materials have their own advantages and disadvantages.

[0007] PE protective film has good flexibility and low cost, suitable for large-scale production, but its texture is relatively soft, easy to deform during the winding process, and insufficient rigidity, prone to shrinkage problems. In addition, the transparency of PE protective film is relatively low, which may affect the subsequent exposure effect.

[0008] PP protective film has high rigidity and excellent transparency, which can better protect the surface of the dry film and provide a clearer exposure effect. However, the PP protective film itself has strong electrostatic properties, which may have an adverse effect on the quality of the dry film during subsequent use, such as adsorbing dust or causing electrostatic discharge damage. In addition, the adhesion of the PP protective film is not stable enough, and unevenness or residue may occur during the peeling process.

[0009] Chinese patent document CN107696652A discloses a protective film for a photosensitive dry film, which is prepared by a multi-layer co-extrusion casting method or a multi-layer co-extrusion stretching method. The protective film includes a middle PP layer and two surface layers, one of which is a PE release layer, and the other is an anti-slip layer; the middle PP layer is completely prepared from PP material; the PE release layer is completely prepared from PE material, and no release agent is added to the surface of the release layer; the anti-slip layer is completely prepared from PE material, or is prepared from a copolymer or blend of PP material and PE material.

[0010] The existing dry film protective film has high static electricity, which can easily have a great impact on the quality of the dry film and has unstable adhesion. Summary of the invention

[0011] In order to solve the deficiencies in the prior art, the purpose of the present invention is to provide an antistatic dry film protective film and a preparation method thereof, which effectively reduces the static electricity accumulation of the dry film protective film and improves the overall performance of the protective film, including better dust and scratch resistance, as well as stable adhesion and easy peelability, thereby extending its service life and improving the efficiency and quality of subsequent processing processes.

[0012] In order to achieve the above object, the present invention adopts the following technical solution:

[0013] The invention discloses an antistatic dry film protective film, which is composited by a matte layer, an adhesive layer and a core layer. The core layer is located between the matte layer and the adhesive layer. The core layer is made of the following components by weight: 60 to 80 parts of copolymerized polypropylene, 18 to 40 parts of polyolefin elastomer and 3 to 10 parts of composite antistatic agent.

[0014] Preferably, the copolymerized polypropylene has an ethylene content of 1 to 15 wt%, a melting point range of 135 to 165° C., and a total molecular weight of 150,000 to 300,000; the polyolefin elastomer is an ethylene-propylene elastomer, and the polyethylene content of the polyolefin elastomer is 8 to 20 wt%.

[0015] Preferably, the matte layer is made of the following components by weight: 100 parts of low-density polyethylene and 1-3 parts of diatomaceous earth; the adhesive layer is made of the following components by weight: 100 parts of low-density polyethylene and 1-3 parts of silicone powder.

[0016] Preferably, the molecular weight of the low-density polyethylene is 100,000 to 300,000.

[0017] Preferably, the thickness of the matte layer is 10 to 30% of the total thickness of the protective film, and the thickness of the adhesive layer is 10 to 30% of the total thickness of the protective film.

[0018] Preferably, the preparation method of the composite antistatic agent comprises the following steps:

[0019] (1) dispersing nano-silicon dioxide in ethanol, adding KH560, adjusting the pH, stirring the reaction, washing and drying the product to obtain pretreated silicon dioxide;

[0020] In the first stage, the surface of silica is modified: nano-silica is reacted with KH560 (γ-glycidyloxypropyltrimethoxysilane) in ethanol. The methoxy group of KH560 is hydrolyzed in the solution to form a silanol group, which then undergoes a condensation reaction with the silanol groups on the surface of silica to form Si-O-Si bonds. After the reaction, epoxy groups are introduced to the surface of silica, providing active sites for subsequent reactions.

[0021] Preferably, in step (1), the pH is adjusted to 4-5; and the stirring reaction conditions are 60-80° C. and stirring the reaction for 2-4 hours.

[0022] Preferably, in step (1), the usage ratio of nano-silicon dioxide, ethanol and KH560 is 10 g: 100-200 mL: 1-5 g.

[0023] (2) dispersing the pretreated silica in DMF, then adding polybenzazole and triethylamine, ultrasonically treating, stirring and reacting under nitrogen protection, filtering, washing and drying the product to obtain grafted silica;

[0024] The second stage is polybenzazole grafting: the pretreated silica is reacted with polybenzazole in DMF. The secondary amine (-NH-) in the polybenzazole molecule undergoes a ring-opening reaction with the epoxy group on the surface of the silica. The epoxy ring opens, and the secondary amine forms a new CN bond with the epoxy group to generate a tertiary amine structure (-N<), while a new hydroxyl group (-OH) is formed on the carbon chain. Triethylamine acts as a catalyst to promote the ring-opening reaction of the epoxy group.

[0025] Preferably, in step (2), the ratio of pretreated silica, polybenzazole and triethylamine is 10g: 2-10g: 0.1-1g; the ultrasonic treatment is performed for 30-60min; and the stirring reaction condition is 80-100°C for 6-12h.

[0026] (3) The grafted silica is dispersed in DMF, methyl methanesulfonate is slowly added dropwise under a nitrogen atmosphere, and potassium carbonate is then added, the reaction is stirred, and the product is filtered, washed with alcohol, and dried to obtain a composite antistatic agent.

[0027] The third stage is quaternization reaction: the grafted silica is reacted with methyl methanesulfonate in DMF. Methyl methanesulfonate, as a strong electrophilic reagent, undergoes quaternization reaction with the tertiary amine generated in the previous step. The nitrogen atom on the tertiary amine attacks the methyl group of methyl methanesulfonate to form an NC bond, and at the same time, the methanesulfonate ion (CH3SO3 - ) as a counter ion to pair with the newly formed quaternary ammonium ion. Potassium carbonate acts as a base to neutralize the acid produced by the reaction, pushing the reaction equilibrium to the right. This three-stage process ultimately produces a composite structure: a silica core with polybenzazole grafted on the surface, and the nitrogen atoms on the polybenzazole are quaternized, resulting in a composite material with excellent antistatic properties.

[0028] Preferably, in step (3), the stirring reaction conditions are: stirring the reaction at 30-50° C. for 12-24 hours; and ultrasonic treatment is performed for 5-10 minutes every 1 hour to accelerate the reaction.

[0029] Preferably, in step (3), the usage ratio of grafted silica, methyl methanesulfonate and potassium carbonate is 10g: 5-10g: 0.1-1g.

[0030] The present invention also claims protection for a method for preparing the antistatic dry film protective film, comprising the following steps: mixing the raw materials according to the formula and melting them respectively through three single-screw extruders, forming a film through a batching block connector, a die head co-extrusion and cooling, and subsequently cooling and shaping the product, thickness detection, online slitting, winding and packaging to obtain the antistatic dry film protective film.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The present invention provides an antistatic dry film protective film, which effectively solves the static electricity problem and the defects of unstable bonding force in the prior art through a three-layer structural design and a special material ratio. The core layer adopts a combination of copolymerized polypropylene, polyolefin elastomer and composite antistatic agent, which not only ensures the rigidity and transparency of the protective film, but also significantly improves the antistatic performance. The introduction of nano-silicon dioxide not only enhances the mechanical strength and thermal stability of the protective film, but also improves the optical properties and dispersibility. The design of the matte layer and the adhesion layer further enhances the functionality of the protective film, improves the bonding stability with the dry film, and ensures good peeling performance. This structural design not only effectively prevents dust adsorption and electrostatic discharge damage, but also improves the overall quality and service life of the dry film.

[0033] 2. The present invention provides a method for preparing a composite antistatic agent. First, nano-silicon dioxide is surface-modified by KH560 to introduce epoxy groups, which provide active sites for subsequent reactions; second, the modified silicon dioxide is reacted with polybenzazole, and the grafting of polybenzazole is achieved by the reaction of the epoxy groups with the secondary amine groups of the polybenzazole to form an electron conduction channel; finally, the grafted polybenzazole is quaternized by methyl methanesulfonate to form a quaternary ammonium salt structure with ion conductivity. This multi-step reaction design ensures that the composite antistatic agent has excellent performance and stability, and realizes the dual mechanism of electronic conduction and ion conduction.

[0034] 3. The present invention provides a composite antistatic agent, in which the grafting of polybenzazole provides an electron conduction channel, effectively reducing the surface resistance; the ionic groups introduced by the quaternization reaction further enhance the charge transmission and dissipation capabilities; at the same time, the three-step modification also improves the compatibility of nano-silica with the resin matrix; the final product not only significantly improves the antistatic performance, but also has good thermal stability and mechanical properties. The synergistic effect of polybenzazole and quaternary ammonium salt creates a multifunctional, efficient and long-lasting antistatic system that can continue to function over a wide frequency range and under different humidity conditions. In addition, this structure also has a certain anti-corrosion ability, further improving the comprehensive performance of the composite material. Therefore, the composite antistatic agent can continue to function during the use of the dry film protective film, effectively prevent static electricity accumulation and discharge damage, and significantly improve the overall quality, reliability and environmental adaptability of the dry film.

[0035] 4. The present invention provides a composite antistatic agent that can form a dense and continuous conductive network in the core layer. This network not only provides a conductive path inside the core layer, but also forms a conductive bridge through the interface between the adjacent layers, allowing the charge to be transferred between different layers. When the film surface is stimulated by external charges, the charge first accumulates in the surface layer, and then is transferred to the core layer through the microscopic discontinuous conductive connection points at the interface between the surface layer and the core layer. The conductive network in the core layer quickly disperses the charge to the entire film layer, preventing the continuous accumulation of surface charge. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0037] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.

[0038] A method for preparing an antistatic dry film protective film comprises the following steps:

[0039] (1) Dispersing 10 g of nano-silicon dioxide into 100-200 mL of ethanol, adding 1-5 g of KH560, adjusting the pH to 4-5, stirring and reacting at 60-80° C. for 2-4 h, washing and drying the product to obtain pretreated silicon dioxide;

[0040] (2) dispersing 10 g of pretreated silica in 100 mL of DMF, then adding 2-10 g of polybenzole and 0.1-1 g of triethylamine, ultrasonically treating for 30-60 min, stirring and reacting at 80-100° C. under nitrogen protection for 6-12 h, filtering, washing, and drying the product to obtain grafted silica;

[0041] (3) Dispersing 10 g of grafted silica in 100 mL of DMF, slowly adding 5-10 g of methyl methanesulfonate dropwise under a nitrogen atmosphere, then adding 0.1-1 g of potassium carbonate, stirring and reacting at 30-50° C. for 12-24 h, performing ultrasonic treatment for 5-10 min every 1 h to accelerate the reaction, filtering the product, washing with alcohol, and drying to obtain a composite antistatic agent;

[0042] (4) After the raw materials are mixed according to the formula, they are melted through three single-screw extruders respectively, and film is formed through a batching block connector, a die head co-extrusion and cooling. The product is subsequently cooled and shaped, thickness tested, online slitting, winding and packaging to obtain the antistatic dry film protective film.

[0043] The core layer is made of the following components by weight: 60-80 parts of copolymerized polypropylene, 18-40 parts of polyolefin elastomer, and 3-10 parts of composite antistatic agent; the matte layer is made of the following components by weight: 100 parts of low-density polyethylene and 1-3 parts of diatomaceous earth; the adhesive layer is made of the following components by weight: 100 parts of low-density polyethylene and 1-3 parts of silicone powder. The thickness of the matte layer is 10-30% of the total thickness of the protective film, and the thickness of the adhesive layer is 10-30% of the total thickness of the protective film.

[0044] Low-density polyethylene was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with a melt flow rate of 3.98 g / 10 min;

[0045] The particle size of nano-silicon dioxide is 20 to 100 nm;

[0046] Diatomite was purchased from Hebei Jiegui Mineral Products Co., Ltd., mesh size: 325-500 mesh;

[0047] The molecular weight of polybenzazole is between 3000 and 1000000;

[0048] The polyolefin elastomer is commercially available, such as polyolefin elastomer with the brand number 6102 from Exxon, polyolefin elastomer with the brand number DF640 from Mitsui & Co., and polyolefin elastomer with the brand number EXACT3139 from Exxon.

[0049] The present invention will be further described below through specific embodiments.

[0050] Example 1

[0051] A method for preparing an antistatic dry film protective film comprises the following steps:

[0052] (1) Dispersing 10 g of nano-silica into 200 mL of ethanol, adding 5 g of KH560, adjusting the pH to 5, stirring and reacting at 80° C. for 2 h, washing and drying the product to obtain pretreated silica;

[0053] (2) Dispersing 10 g of pretreated silica in 100 mL of DMF, then adding 10 g of polybenzazole and 1 g of triethylamine, ultrasonically treating for 60 min, stirring and reacting at 100 ° C. under nitrogen protection for 6 h, filtering, washing, and drying the product to obtain grafted silica;

[0054] (3) 10 g of grafted silica was dispersed in 100 mL of DMF, 10 g of methyl methanesulfonate was slowly added dropwise under a nitrogen atmosphere, and then 1 g of potassium carbonate was added, and the mixture was stirred at 50° C. for 12 h, and ultrasonic treatment was performed for 10 min every 1 h to accelerate the reaction. The product was filtered, washed with alcohol, and dried to obtain a composite antistatic agent;

[0055] (4) After the raw materials are mixed according to the formula, they are melted through three single-screw extruders respectively, and film is formed through a batching block connector, a die head co-extrusion and cooling. The product is subsequently cooled and shaped, thickness tested, online slitting, winding and packaging to obtain the antistatic dry film protective film.

[0056] The core layer is made of the following components by weight: 80g of copolymerized polypropylene, 40g of polyolefin elastomer, and 10g of composite antistatic agent; the matte layer is made of the following components by weight: 100g of low-density polyethylene and 3g of diatomaceous earth; the adhesive layer is made of the following components by weight: 100g of low-density polyethylene and 3g of silicone powder. The thickness of the matte layer is 30% of the total thickness of the protective film, and the thickness of the adhesive layer is 30% of the total thickness of the protective film.

[0057] Example 2

[0058] A method for preparing an antistatic dry film protective film comprises the following steps:

[0059] (1) Dispersing 10 g of nano-silica into 100 mL of ethanol, adding 4 g of KH560, adjusting the pH to 4.5, stirring and reacting at 70° C. for 3 h, washing and drying the product to obtain pretreated silica;

[0060] (2) Dispersing 10 g of pretreated silica in 100 mL of DMF, then adding 8 g of polybenzazole and 0.8 g of triethylamine, ultrasonically treating for 50 min, stirring and reacting at 90 ° C. under nitrogen protection for 10 h, filtering, washing, and drying the product to obtain grafted silica;

[0061] (3) 10 g of grafted silica was dispersed in 100 mL of DMF, 8 g of methyl methanesulfonate was slowly added dropwise under a nitrogen atmosphere, and then 0.8 g of potassium carbonate was added, and the mixture was stirred at 40° C. for 20 h, and ultrasonic treatment was performed for 10 min every 1 h to accelerate the reaction. The product was filtered, washed with alcohol, and dried to obtain a composite antistatic agent;

[0062] (4) After the raw materials are mixed according to the formula, they are melted through three single-screw extruders respectively, and film is formed through a batching block connector, a die head co-extrusion and cooling. The product is subsequently cooled and shaped, thickness tested, online slitting, winding and packaging to obtain the antistatic dry film protective film.

[0063] The core layer is made of the following components by weight: 75g copolymerized polypropylene, 35g polyolefin elastomer, and 8g composite antistatic agent; the matte layer is made of the following components by weight: 100g low-density polyethylene and 2g diatomaceous earth; the adhesive layer is made of the following components by weight: 100g low-density polyethylene and 2g silicone powder. The thickness of the matte layer is 30% of the total thickness of the protective film, and the thickness of the adhesive layer is 30% of the total thickness of the protective film.

[0064] Example 3

[0065] A method for preparing an antistatic dry film protective film comprises the following steps:

[0066] (1) Dispersing 10 g of nano-silica into 100 mL of ethanol, adding 3 g of KH560, adjusting the pH to 4.5, stirring and reacting at 70° C. for 3 h, washing and drying the product to obtain pretreated silica;

[0067] (2) Dispersing 10 g of pretreated silica in 100 mL of DMF, then adding 6 g of polybenzazole and 0.4 g of triethylamine, ultrasonically treating for 40 min, stirring and reacting at 90 ° C. under nitrogen protection for 8 h, filtering, washing, and drying the product to obtain grafted silica;

[0068] (3) 10 g of grafted silica was dispersed in 100 mL of DMF, 7 g of methyl methanesulfonate was slowly added dropwise under a nitrogen atmosphere, and then 0.4 g of potassium carbonate was added, and the mixture was stirred at 40° C. for 16 h, and ultrasonic treatment was performed for 10 min every 1 h to accelerate the reaction. The product was filtered, washed with alcohol, and dried to obtain a composite antistatic agent;

[0069] (4) After the raw materials are mixed according to the formula, they are melted through three single-screw extruders respectively, and film is formed through a batching block connector, a die head co-extrusion and cooling. The product is subsequently cooled and shaped, thickness tested, online slitting, winding and packaging to obtain the antistatic dry film protective film.

[0070] The core layer is made of the following components by weight: 70g copolymerized polypropylene, 30g polyolefin elastomer, and 5g composite antistatic agent; the matte layer is made of the following components by weight: 100g low-density polyethylene and 2g diatomaceous earth; the adhesive layer is made of the following components by weight: 100g low-density polyethylene and 2g silicone powder. The thickness of the matte layer is 30% of the total thickness of the protective film, and the thickness of the adhesive layer is 30% of the total thickness of the protective film.

[0071] Example 4

[0072] A method for preparing an antistatic dry film protective film comprises the following steps:

[0073] (1) Dispersing 10 g of nano-silica into 100 mL of ethanol, adding 1 g of KH560, adjusting the pH to 4, stirring and reacting at 60° C. for 4 h, washing and drying the product to obtain pretreated silica;

[0074] (2) 10 g of pretreated silica was dispersed in 100 mL of DMF, and then 2 g of polybenzazole and 0.1 g of triethylamine were added, and the mixture was ultrasonically treated for 30 min. The mixture was stirred and reacted at 80 ° C. under nitrogen protection for 12 h. The product was filtered, washed, and dried to obtain grafted silica.

[0075] (3) 10 g of grafted silica was dispersed in 100 mL of DMF, 5 g of methyl methanesulfonate was slowly added dropwise under a nitrogen atmosphere, and then 0.1 g of potassium carbonate was added, and the mixture was stirred at 30° C. for 24 h, and ultrasonic treatment was performed for 10 min every 1 h to accelerate the reaction. The product was filtered, washed with alcohol, and dried to obtain a composite antistatic agent;

[0076] (4) After the raw materials are mixed according to the formula, they are melted through three single-screw extruders respectively, and film is formed through a batching block connector, a die head co-extrusion and cooling. The product is subsequently cooled and shaped, thickness tested, online slitting, winding and packaging to obtain the antistatic dry film protective film.

[0077] The core layer is made of the following components by weight: 60g of copolymerized polypropylene, 18g of polyolefin elastomer, and 3g of composite antistatic agent; the matte layer is made of the following components by weight: 100g of low-density polyethylene and 1g of diatomaceous earth; the adhesive layer is made of the following components by weight: 100g of low-density polyethylene and 1g of silicone powder. The thickness of the matte layer is 30% of the total thickness of the protective film, and the thickness of the adhesive layer is 30% of the total thickness of the protective film.

[0078] Comparative Example 1

[0079] A method for preparing a dry film protective film comprises the following steps:

[0080] (1) Dispersing 10 g of nano-silica into 200 mL of ethanol, adding 5 g of KH560, adjusting the pH to 5, stirring and reacting at 80° C. for 2 h, washing and drying the product to obtain pretreated silica;

[0081] (2) Dispersing 10 g of pretreated silica in 100 mL of DMF, then adding 10 g of polybenzazole and 1 g of triethylamine, ultrasonically treating for 60 min, stirring and reacting at 100 ° C. under nitrogen protection for 6 h, filtering, washing, and drying the product to obtain grafted silica;

[0082] (3) After the raw materials are mixed according to the formula, they are melted through three single-screw extruders respectively, and then formed into films through a batching block connector, a die head co-extrusion and cooling. The product is subsequently cooled and shaped, thickness tested, online slitting, winding and packaging to obtain the dry film protective film.

[0083] The core layer is made of the following components by weight: 80g of copolymerized polypropylene, 40g of polyolefin elastomer, and 10g of grafted silica; the matte layer is made of the following components by weight: 100g of low-density polyethylene and 3g of diatomaceous earth; the adhesive layer is made of the following components by weight: 100g of low-density polyethylene and 3g of silicone powder. The thickness of the matte layer is 30% of the total thickness of the protective film, and the thickness of the adhesive layer is 30% of the total thickness of the protective film.

[0084] Comparative Example 2

[0085] A method for preparing a dry film protective film comprises the following steps:

[0086] (1) Dispersing 10 g of nano-silica into 200 mL of ethanol, adding 5 g of KH560, adjusting the pH to 5, stirring and reacting at 80° C. for 2 h, washing and drying the product to obtain pretreated silica;

[0087] (2) The raw materials are mixed according to the formula and melted through three single-screw extruders respectively, and then formed into a film through a batching block connector, a die head co-extrusion and cooling. The product is subsequently cooled and shaped, thickness tested, online slitting, winding and packaging to obtain the dry film protective film.

[0088] The core layer is made of the following components by weight: 80g of copolymerized polypropylene, 40g of polyolefin elastomer, and 10g of pretreated silica; the matte layer is made of the following components by weight: 100g of low-density polyethylene and 3g of diatomaceous earth; the adhesive layer is made of the following components by weight: 100g of low-density polyethylene and 3g of silicone powder. The thickness of the matte layer is 30% of the total thickness of the protective film, and the thickness of the adhesive layer is 30% of the total thickness of the protective film.

[0089] The dry film protective films prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were tested for performance. The thickness of the protective film was measured with reference to GB / T6672-2001 "Mechanical measurement method for thickness of plastic films and sheets", the tensile strength and elongation at break were tested with reference to GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets", the transmittance was tested with reference to GB / T2410-2008 "Determination of light transmittance and haze of transparent plastics", and the surface resistance was tested with reference to GB / T31838.2-2019 "Dielectric and resistive properties of solid insulating materials Part 2: Resistive properties (DC method) Volume resistance and volume resistivity", and the protective films were tested one week after production and three months after production. Specific data are shown in Table 1.

[0090] Table 1 Dry film protective film performance test results

[0091]

[0092] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An antistatic dry film protective film, composed of a matte layer, an adhesive layer, and a core layer, wherein the core layer is located between the matte layer and the adhesive layer, characterized in that: The core layer is made of the following components in parts by weight: 60-80 parts of copolymerized polypropylene, 18-40 parts of polyolefin elastomer, and 3-10 parts of composite antistatic agent.

2. The dry film protective film according to claim 1, characterized in that: The copolymerized polypropylene has an ethylene content of 1 to 15 wt%, a melting point range of 135 to 165° C., and a total molecular weight of 100,000 to 300,000. The polyolefin elastomer is an ethylene-propylene elastomer, and the polyethylene content in the polyolefin elastomer is 8 to 20 wt%.

3. The dry film protective film according to claim 1, characterized in that: The matte layer is made of the following components in parts by weight: 100 parts of low-density polyethylene and 1 to 3 parts of diatomaceous earth; the adhesion layer is made of the following components in parts by weight: 100 parts of low-density polyethylene and 1 to 3 parts of silicone powder; the molecular weight of the low-density polyethylene is 100,000 to 300,000; the thickness of the matte layer is 10 to 30% of the total thickness of the protective film, and the thickness of the adhesion layer is 10 to 30% of the total thickness of the protective film.

4. The dry film protective film according to claim 1, characterized in that: The preparation method of the composite antistatic agent comprises the following steps: (1) dispersing nano-silica in ethanol, adding KH560, adjusting the pH, stirring the reaction, washing and drying the product to obtain pretreated silica; (2) dispersing the pretreated silica in DMF, then adding polybenzazole and triethylamine, ultrasonically treating, stirring and reacting under nitrogen protection, filtering, washing, and drying the product to obtain grafted silica; (3) Grafted silica is dispersed in DMF, methyl methanesulfonate is slowly added dropwise under a nitrogen atmosphere, followed by potassium carbonate, and the mixture is stirred for reaction. The product is filtered, washed with alcohol, and dried to obtain a composite antistatic agent.

5. The dry film protective film according to claim 4, characterized in that: In step (1), the pH is adjusted to 4-5; and the stirring reaction conditions are 60-80° C. and 2-4 h.

6. The dry film protective film according to claim 4, characterized in that: In step (1), the usage ratio of nano-silica, ethanol and KH560 is 10 g: 100-200 mL: 1-5 g.

7. The dry film protective film according to claim 4, characterized in that: In step (2), the ratio of pretreated silica, polybenzazole and triethylamine is 10g: 2-10g: 0.1-1g; ultrasonic treatment is performed for 30-60min; and the stirring reaction condition is 80-100°C and the stirring reaction is performed for 6-12h.

8. The dry film protective film according to claim 4, characterized in that: In step (3), the stirring reaction conditions are 30-50° C. for 12-24 hours; and ultrasonic treatment is performed for 5-10 minutes every hour to accelerate the reaction.

9. The dry film protective film according to claim 4, characterized in that: In step (3), the usage ratio of grafted silica, methyl methanesulfonate and potassium carbonate is 10g:5-10g:0.1-1g.

10. A method for preparing the antistatic dry film protective film according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing the raw materials according to the formula and melting them respectively through three single-screw extruders, co-extruding and cooling through a batching block connector and a die head to form a film, and subsequently cooling and shaping the product, thickness detection, online slitting, winding and packaging to obtain the antistatic dry film protective film.